Spiritual care interventions in critical area: A literature review study - Theresia, Siwi Ikaristi Maria (Mikki: Majalah Ilmu Keperawatan dan Kesehatan Indonesia, 2022)
Background: Spiritual care for patients in critical areas is urgently required due to anxiety and fear related to death. Most people think that physical intervention is more important for patient care. However, spiritual needs are considered beneficial to speed up the physical recovery process and reduce pain. Nurse intervention for the provision of spiritual need to be an important aspect and expected at any time since the care is inseparable in critical care setting. Objective: This literature review aims to identify various spiritual care interventions for patients in critical areas.Method: A literature review conducted to discover spiritual care interventions. Data were collected in September 2022 from PubMed and Google Scholar database. A total of 3 (three) relevant studies were included in this study.Result: The articles are qualitative and quantitative study which were conducted in 2021 and 2022. Sample in the studies ranged from 19 to 47 respondents, including nurses who work in critical settings, religious leaders and patient’s families. Various nurse-led intervention to fulfill patient’s spiritual needs are provision of belief, create calm atmosphere during prayer time, Facilitate placement of patients and their families’ trusted protection symbol, collaboration with religious leaders and use of virtual technology for communication purpose.Conclusion: Nurse did not neglect spiritual care for patients treated in critical areas. Consistent behavior to respect and support patient’s spiritual needs in accordance with the religion and beliefs of the patient demonstrated by the nurses.